Contamination of dining tables with pesticides in Kibrigwi irrigation scheme - Kimani, V.W.; McDermott, John J. (Kenya Agricultural Research Institute, 1999)
Kibirigwi Irrigation Scheme is a smallholder farming area in Central Kenya, where the main activity is production of horticultural crops. Pesticides are widely misused. This study investigated the extent of household pesticide exposure in 40 randomly selected farms in July-August, 1995. Exposure measures collected included pesticide levels on dining table swabs. Fifty cotton clothes measuring 30 cm*30 cm were prepared in the laboratory by soaking overnight in methanol. In each of the 40 selected homesteads, the table used for meals was swabbed with a piece of cloth. In the laboratory, the residuals chemicals extracted from these swabs using conventional residue analysis procedures and the extracts were analysed by gas liquid chromatography. Information on which pesticide (s) were recently handled in the home and when, were also recorded. Cypermethrin (9/40), malathion (9/40), Diazinon (5/40), dimethoate (4/40), chloropyrifos (4/40) and fenitrothion (1/40) were detected in these samples. The range of individual organophosphate pesticides detected was 0.01-8.7 ug/cm2 of table area and for cypermethrin the range was 0.0024 ng-5.8 ng/cm2. It was concluded that farmers and their family members are likely to be contaminated with pesticides from tables either dermally or through contamination of food placed on such tables.